Lysozyme Inhibitors as Tools for Lysozyme Profiling: Identification and Antibacterial Function of Lysozymes in the Hemolymph of the Blue Mussel - Lise Vanderkelen; Joris M. Van Herreweghe; Chris W. Michiels (Molecules, 2023)
Lysozymes are universal components of the innate immune system of animals that kill bacteria by hydrolyzing their main cell wall polymer, peptidoglycan. Three main families of lysozyme have been identified, designated as chicken (c)-, goose (g)- and invertebrate (i)-type. In response, bacteria have evolved specific protein inhibitors against each of the three lysozyme families. In this study, we developed a serial array of three affinity matrices functionalized with a c-, g-, and i-type inhibitors for lysozyme typing, i.e., to detect and differentiate lysozymes in fluids or extracts from animals. The tool was validated on the blue mussel (Mytilus edulis), whose genome carries multiple putative i-, g-, and c-type lysozyme genes. Hemolymph plasma of the animals was found to contain both i- and g-type, but not c-type lysozyme. Furthermore, hemolymph survival of Aeromonas hydrophila and E. coli strains lacking or overproducing the i- type or g-type lysozyme inhibitor, respectively, was analyzed to study the role of the two lysozymes in innate immunity. The results demonstrated an active role for the g-type lysozyme in the innate immunity of the blue mussel, but failed to show a contribution by the i-type lysozyme. Lysozyme profiling using inhibitor-based affinity chromatography will be a useful novel tool for studying animal innate immunity.